Fatty Acid Profile of Pig Meat after Probiotic Administration - Ross, Gloria Romina (2012)
The aim of this work was to study the fatty acid proﬁle of pig meat after probiotic administration. Thirty postweaned pigs (25 day old) were distributed into 2 groups: control (n = 15) and probiotic (n = 15). Each experimental group was fed ad libitum on a commercial diet for 35 days. Lactobacillus amylovorus and Enterococcus faecium mixed culture (108 CFU/ml) was daily orally delivered to the probiotic group. At the end of the assay, six pigs randomly selected from each group were slaughtered and muscle samples (Longissimus dorsi) were taken for fatty acid analysis. Tissues from the probiotic group animals exhibited an increase in monounsaturated and polyunsaturated fatty acids; furthermore, linoleic acid (C18:2), linolenic acid (18:3), and cis-9,trans-11 conjugated linoleic acid (CLA) concentrations were signiﬁcantly higher (p < 0.05) compared to the control group. These results suggest probiotic administration could be useful to modify and improve the fatty acid proﬁle of pig meat.